Antimicrobial resistance patterns of commensal Escherichia coli isolated from feces of non-diarrheic dogs in Grenada, West Indies - Amadi, Victor A. (Vet World, 2019)
BACKGROUND AND AIM: There is currently no published information on the prevalence and antimicrobial susceptibility patterns of commensal Escherichia coli in dogs of Grenada origin. Monitoring antimicrobial resistance helps in the empirical selection of antibiotics. This study determined the occurrence of E. coli including the O157:H7 serotype in feces of non-diarrheic dogs of Grenada origin and the antibiotic resistance pattern of the E. coli isolates. MATERIALS AND METHODS: Fecal samples from 142 of the 144 (98.6%) dogs were culture positive for E. coli. Selection of up to three colonies from each of the 142 E. coli-positive samples yielded a total of 402 E. coli isolates, which were analyzed for the presence of non-sorbitol fermenting colonies, and O157-agglutination. RESULTS: Of the 402 E. coli isolates, 30 (7.5%) were non-sorbitol fermenters. However, none of the 402 isolates gave a positive reaction (O157:H7) to the E. coli O157:H7 latex kit. Antimicrobial susceptibility tests against 12 antibiotics revealed low resistance rates to all the tested antibiotics except for tetracycline (Te) (23.4%), cephalothin (CF) (13.2%), and ampicillin (AM) (7.7%). Thirty-nine out of the 402 (9.7%), E. coli isolates were resistant to two or more antibiotics of different classes. CONCLUSION: This is the first report of isolation and antimicrobial susceptibilities of commensal E. coli from non-diarrheic dogs in Grenada. Some of the isolates (39/402 isolates, 9.7%) were resistant to multiple antibiotics. This study showed that presently, dogs in Grenada should not be considered a reservoir for the E. coli O157:H7 serotype and for multiple antibiotic-resistant E. coli strains. Among the 402 E. coli isolates, the resistance rate to drugs other than Te, CF, and AM was very low.